Deciphering the anthocyanin metabolism gene network in tea plant (Camellia sinensis) through structural equation modeling - Pan Xia; Mei Chen; Linbo Chen; Yijian Yang; Ling Ma; Pinpin Bi; Song Tang; Qiongxian Luo; Jiwei Chen; Hongwei Chen; Hongling Zhang (BMC Genomics)
Abstract Background Tea is an important cash crop that significantly contributes to rural development, poverty reduction and food security in many developing countries. It provides livelihoods for millions of smallholder producers and aids their economic stability. Anthocyanins in tea leaves provides excellent commercial quality and germplasm exploration potential. These compounds give tea leaves vibrant colors and increase health benefits. The current understanding of the synergistic regulation mechanisms responsible for color changes in purple tea, attributed to anthocyanin degradation, remains unclear. Results In this study, we have identified 30 gene families within the genome that are associated to with anthocyanin metabolism from tea. These gene families play distinct roles in the biosynthesis of anthocyanin including the formation of the core, structure, modification of the molecular framework, facilitation of transport process, regulation of gene expression, breakdown pathways, sugar transportation and iron ion respectively. Subsequently, we investigated the synergistic mechanisms of anthocyanin metabolism related gene families within tea leaves using structural equation modeling. The results showed that sugar transport positively affects anthocyanin transportation, and promotes anthocyanin degradation during leaf pigmentation, whereas, it inhibits anthocyanin degradation during the fading of leaf color. Further, Iron ions facilitate the degradation of anthocyanins during their deposition and conversely, impede this degradation process during digestion. These finding suggests that tea plants may regulate the synthesis and degradation of anthocyanins through sugar transport and iron ions ensure healthy levels and vibrant colors. Conclusions Our study contributes valuable information into the dynamic equilibrium anthocyanin mechanism and sheds light on complex regulatory mechanisms that govern the synthesis, transport and degradation of these pigments. These insights could be further used to develop strategies for enhancing anthocyanins content in unique tea germplasm to aid tea industry in producing new tea products with increased health benefits and aesthetic appeals.